DEVELOPMENT OF A KNOWLEDGE MANAGEMENT MODEL FOR SMALL AND MEDIUM-SIZED TEXTILE SECTOR IN THE CITY OF RIOBAMBA - Arguello Mendoza, Carlos Patricio (2017)
SMEs in Ecuador are particularly involved in the production of goods and services (ALADI 2001), being the basis of the social development of the country both producing, demanding and buying products or adding added value, so that they constitute a fundamental actor These organizations represent 95% of the productive units of the country, generate 60% of the employment, participate in the 50% of production, have a large redistributive potential, important capacity for job creation, broad adaptability and flexibility in the face of change.The research carried out designs a Knowledge Management Model for this important sector of the national economy, taking as a unit of study the supply chain of SMEs in the textile sector of the city of Riobamba, based on two variables, Knowledge Management With three dimensions: Strategic Management of Knowledge, Innovative Environment and Knowledge Cycle or Functional Management of Knowledge and a Dependent variable that is the Perception of Results of the system has been defined for the purposes of this study, as the formulation of judgments about reality In this case, the CMI Integral Control Panel in its dimensions of innovation, improvement of internal processes, relations with the environment and economic, to which was added a reference comparison with companies and workers with Functions.